Leadership and Research Performance : The Consequences of Micromanagement in Academic Settings - Mishra, Namrata; Rajkumar, M.; Mishra, Rajiv (Prabandhan: Indian Journal of Management, 2025)
Purpose : The aim was to determine the factors of micromanagement leadership and its influence on the research performance of teaching faculty. Methodology : Primary research was used to build the research and publication performance model. To collect data and evaluate the model, a structured questionnaire was used to acquire a sample size of 160 respondents. Sampling involved stratified random sampling of higher educational institutions in Delhi/NCR from the AISHE 2021–2022 report, and the respondents were selected based on judgment sampling. Factor analysis, correlation, and multiple regression using SPSS were used to test the model. Findings : The factor analysis showed that micromanagement leadership has five factors: Delegation/Decision-Making, Delayed Process, Meeting and Reporting, Closed Supervision, and Autonomy. A further regression model suggested that all five factors of micromanagement leadership influenced the research performance of teaching faculty, with Delegation/Decision-Making being the most significant. Practical Implications : To better explain the research performance, it may be necessary to examine other variables or look for better assessments of the constructs. This study did not include factors that affected the performance of teaching faculty, such as teaching and administrative roles. Originality : Unlike prior research on leadership and performance, this study focused on micromanagement leadership and its influence on research performance.